2021
DOI: 10.1093/milmed/usaa233
|View full text |Cite
|
Sign up to set email alerts
|

Case Series of Arterial Gas Embolism Incidents in U.S. Navy Pressurized Submarine Escape Training From 2018 to 2019

Abstract: The goal of Pressurized Submarine Escape Training (PSET) is to prepare future submariners for the physical and mental challenges of escaping a disabled submarine and promote proper handling of the Beaufort Ltd Mk 11 Submarine Escape and Immersion Equipment suit. Training participants are only permitted to enter PSET after strict health screening protocols have been met to optimize trainees’ safety. Before PSET, trainees are given detailed, one-on-one instruction on proper ascent mechanics by specially trained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In order for such a serious scenario to be carried out in accordance with its purpose, it was expected that the anxiety levels of the trainees will increase slightly, as the results of this research showed [53]. However, if this increase in the anxiety level of the trainees is not observed carefully by the trainers, it may cause unwanted accidents and injuries [18,28,29,54], even if the necessary precautions are taken in accordance with the OPITO standards in the trainings.…”
Section: Discussionmentioning
confidence: 97%
“…In order for such a serious scenario to be carried out in accordance with its purpose, it was expected that the anxiety levels of the trainees will increase slightly, as the results of this research showed [53]. However, if this increase in the anxiety level of the trainees is not observed carefully by the trainers, it may cause unwanted accidents and injuries [18,28,29,54], even if the necessary precautions are taken in accordance with the OPITO standards in the trainings.…”
Section: Discussionmentioning
confidence: 97%